CAN OF SPINACH, a novel long non-coding RNA, affects iron deficiency responses in Arabidopsis thaliana - Bakirbas, Ahmet; Walker, Elsbeth L. (Frontiers in Plant Science, 2022)
Long non-coding RNAs (lncRNAs) are RNA molecules with functions independent of any protein-coding potential. A whole transcriptome (RNA-seq) study of Arabidopsis shoots under iron sufficient and deficient conditions was carried out to determine the genes that are iron-regulated in the shoots. We identified two previously unannotated transcripts on chromosome 1 that are significantly iron-regulated. We have called this iron-regulated lncRNA, CAN OF SPINACH (COS). cos mutants have altered iron levels in leaves and seeds. Despite the low iron levels in the leaves, cos mutants have higher chlorophyll levels than WT plants. Moreover, cos mutants have abnormal development during iron deficiency. Roots of cos mutants are longer than those of WT plants, when grown on iron deficient medium. In addition, cos mutant plants accumulate singlet oxygen during iron deficiency. The mechanism through which COS affects iron deficiency responses is unclear, but small regions of sequence similarity to several genes involved in iron deficiency responses occur in COS, and small RNAs from these regions have been detected. We hypothesize that COS is required for normal adaptation to iron deficiency conditions.